Caracterización de aislamientos de Xanthomonas campestris pv. phaseoli (XCP) - Rodriguez, O.=700 1 Faure, B.; Corrales, M.A.P.; Otoya, M.M.; Nápoles, P.; Cuéllar, I.
Sumarios (Es, En)
5 ref.
Keywords: PHASEOLUS VULGARIS; XANTHOMONAS CAMPESTRIS; BACTERIOSIS; ORGANISMOS PATOGENOS; CUBA